2017
DOI: 10.1080/10641963.2016.1226887
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to angiotensin II increases blood pressure and decreases salt sensitivity in rats

Abstract: Renin angiotensin aldosterone system (RAAS) plays an essential role in the homeostatic control of arterial blood pressure, perfusion of tissues, and control of extracellular fluid. Its components are highly expressed in the developing kidney, general vasculature, brain, and heart. A modified intrauterine environment alters mechanisms controlling blood pressure (BP) and can lead to hypertension in the adult offspring and developmentally programmed RAAS can be involved in this process. There are very little data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…In our study, AngII animals have been reported to have increased plasma aldosterone levels compared to controls (Svitok et al 2017), also observed in transgenic rats (TGR(mRen2)27) with upregulated RAAS. Aldosterone levels were found to be 10-times higher in rats with upregulated RAAS than in control rats, which supports upregulation of the renin-angiotensin system, as it is well known that angiotensin II stimulates aldosterone synthesis (Ferrario 1983;Zeman et al 2007).…”
Section: A B Csupporting
confidence: 72%
See 2 more Smart Citations
“…In our study, AngII animals have been reported to have increased plasma aldosterone levels compared to controls (Svitok et al 2017), also observed in transgenic rats (TGR(mRen2)27) with upregulated RAAS. Aldosterone levels were found to be 10-times higher in rats with upregulated RAAS than in control rats, which supports upregulation of the renin-angiotensin system, as it is well known that angiotensin II stimulates aldosterone synthesis (Ferrario 1983;Zeman et al 2007).…”
Section: A B Csupporting
confidence: 72%
“…research presented here is part of a larger project focused on the effects of prenatal activation of regulatory mechanisms of blood pressure, part of which has already been published (Svitok et al 2017). We hypothesised that the activation of maternal RAAS (via higher levels of angiotensin II) would be associated with changes in the social coping behaviour of the offspring.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find significant changes in the kidney after increased salt intake and this finding is in agreement with data on BP in our previous study. 18 Surprisingly, the progeny of Ang II treated mothers displayed a decreased sensitivity of BP to salt. The absence of negative effects of higher salt diet was not expected but can be explained by a moderately increased (2%) salt content, which is still in a physiological range.…”
Section: Discussionmentioning
confidence: 99%
“…17 Moreover, in our previous study we demonstrated that exposure of pregnant rats to increased Ang II altered postnatal development and increased BP in offspring. 18 These changes were associated with increased aldosterone levels and decreased renin activity in the circulation, 18 but physiological mechanisms behind this phenomenon are not fully explained. Angiotensin II increases expression of cytokines, inflammatory and fibrotic factors that affect renal hemodynamics, and leads to the development of glomerular damage.…”
Section: Introductionmentioning
confidence: 99%